Drugs, society & human behavior - Hart, Carl L.; Ksir, Charles (New York McGraw Hill, 2022)
"This text approaches drugs and drug use from a variety of perspectives-behavioral, pharmacological, historical, social, legal, and clinical-which will help students connect the content to their own interests"--
Includes bibliographical references and index.
Keywords: Drugs of abuse; Drugs -- Social aspects; Neuropsychopharmacology